Gut-Brain Axis Dysfunction in Parkinson's Disease: Early Biomarkers and Therapeutic Potential in Jakarta, Indonesia - Zahra Amir; Wisnu Wardhana Putra; Linda Purnama; Saurie Hernandez; Adolfo Rawlings; Immanuel Simbolon (Sriwijaya Journal of Neurology, 2023)
Introduction: Parkinson's disease (PD) is a neurodegenerative disorder characterized by motor and non-motor symptoms. Increasing evidence suggests a crucial role of gut-brain axis dysfunction in PD pathogenesis. This study aimed to investigate the gut microbiome composition, identify potential early biomarkers, and explore the therapeutic potential of targeting the gut-brain axis in PD patients in Jakarta, Indonesia. Methods: This cross-sectional study involved 50 PD patients and 50 age-matched healthy controls from Jakarta. Stool and blood samples were collected for 16S rRNA gene sequencing to analyze gut microbiome composition, and serum inflammatory markers (TNF-α, IL-6, and CRP) were measured using ELISA. Clinical data, including disease duration, severity, and non-motor symptoms, were assessed using standardized scales. Results: PD patients exhibited significant alterations in gut microbiome composition compared to controls, with a decrease in beneficial bacteria (e.g., Faecalibacterium prausnitzii) and an increase in pro-inflammatory bacteria (e.g., Enterobacteriaceae). Elevated levels of serum inflammatory markers were also observed in PD patients. Correlation analysis revealed associations between specific gut microbiota, inflammatory markers, and disease severity. Conclusion: This study provides evidence of gut-brain axis dysfunction in PD patients in Jakarta, Indonesia. Alterations in gut microbiome composition and increased systemic inflammation may serve as potential early biomarkers and therapeutic targets for PD. Further research is needed to explore the causal relationship and develop targeted interventions.